Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.2514/1.j057056
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Bifurcation Phenomenon on Supersonic Blowing Trailing Edges

Abstract: Turbine blades operating in transonic-supersonic regime develop a complex shock wave system at the trailing edge, a phenomenon that leads to unfavorable pressure perturbations downstream and can interact with other turbine stages. Understanding the fluid behavior of the area adjacent to the trailing edge is essential in order to determine the parameters that have influence on these pressure fluctuations. Colder flow, bled from the high-pressure compressor, is often purged at the trailing edge to cool the thin … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 38 publications
2
17
0
Order By: Relevance
“…6-right). This flow system has been carefully studied in the past [11,14], so it is briefly described here. As the boundary layers of upper and lower sides approach the trailing edge, they separate forming two symmetric shear layers that confine a subsonic recirculation area, the base region.…”
Section: Supersonic Flowmentioning
confidence: 99%
See 1 more Smart Citation
“…6-right). This flow system has been carefully studied in the past [11,14], so it is briefly described here. As the boundary layers of upper and lower sides approach the trailing edge, they separate forming two symmetric shear layers that confine a subsonic recirculation area, the base region.…”
Section: Supersonic Flowmentioning
confidence: 99%
“…However, as it was found by Saracoglu et al [11], the injection of flow in the base region can lead to the apparition of non-symmetrical configurations related to a bifurcation phenomena associated to the intensity of the injected flow ( Fig.2). Based on those results, Martinez-Cava et al [14] performed a detailed study of a simplified turbine trailing edge combining RANS simulations and global stability analysis. Results showed that for jet intensities above certain value, a difference in pressure between the upper and lower sides of the trailing edge will appear, forcing the flow to change its direction through an induced Coanda effect.…”
Section: Introductionmentioning
confidence: 99%
“…As a final test case, we consider the EVP arising in the study of the flow in refrigerated turbine stages whenever supersonic jets blowing from the blade trailing edge are used as cooling strategy. The detailed study of this configuration and a description of its complex flow topology can be found in References , and . Their investigation aims to understand the flow behavior in turbine blades operating in the transonic‐supersonic regime: a complex shock wave system is established at the trailing edge.…”
Section: An Industrial Application Of Dr: Pressure Bifurcation Phenommentioning
confidence: 99%
“…Under certain circumstances, the purged flow generates nonsymmetrical configurations due to the pressure imbalance provoked by the injected flow. Martinez‐Cava et al and Wang et al combined RANS simulations and global stability analysis to investigate the physical reasons behind this flow bifurcation. An antisymmetric global mode was ultimately identified as the responsible of triggering the main mechanism forcing the changes in the flow topology.…”
Section: An Industrial Application Of Dr: Pressure Bifurcation Phenommentioning
confidence: 99%
See 1 more Smart Citation